2018
DOI: 10.1001/jamasurg.2018.2721
|View full text |Cite
|
Sign up to set email alerts
|

Association of Preoperative Antiviral Treatment With Incidences of Microvascular Invasion and Early Tumor Recurrence in Hepatitis B Virus–Related Hepatocellular Carcinoma

Abstract: A high preoperative HBV DNA level was an independent risk factor of MVI. Antiviral treatment administered more than 90 days before surgery was associated with reduced incidences of MVI and early tumor recurrence after partial hepatectomy for HBV-related HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 56 publications
1
67
0
Order By: Relevance
“…Our study covers both patients with viral hepatitis and non-viral hepatitis, while the majority of previous studies focus on HBV-related HCC [ 33 , 42 , 43 ]. ROC curves in subgroup analysis shows relatively satisfactory discriminative performance of the nomogram model regardless of the HBV infection status, indicating that our findings might be comparably suitable for HCC developed from both viral hepatitis and non-viral hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Our study covers both patients with viral hepatitis and non-viral hepatitis, while the majority of previous studies focus on HBV-related HCC [ 33 , 42 , 43 ]. ROC curves in subgroup analysis shows relatively satisfactory discriminative performance of the nomogram model regardless of the HBV infection status, indicating that our findings might be comparably suitable for HCC developed from both viral hepatitis and non-viral hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a study of 2,362 patients who underwent resection for CHB-related HCC (326 patients receiving antiviral treatment; 2,036 not receiving antiviral treatment), Li et al found that the group with antiviral treatment had better survival than the control group (5-year overall survival rate 69.1% vs. 56.3%; p <0.001). 27 Interestingly, post-HCC NA, which may be regarded as a 'delay' in suppressing the virus, had benefited HCC patients in a similar degree to those who had been taking NA before HCC occurrence. This observation gives a positive motivation to doctors and patients that it is never too late to start NA treatment as tertiary prophylaxis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The cut‐off value of HBV‐DNA load was defined as depicted in a previous paper . Microvascular invasion(MVI) was determined based upon tumor cell nests present in small branches of hepatic and portal veins and lymphatic ducts on microscopy .…”
Section: Methodsmentioning
confidence: 99%